Great essays in science - Gardner, Martin, 1914- (Buffalo, N.Y. : Prometheus Books, 1994)
Thirty-four essays discuss fundamental aspects of modern science.
"Isaac Asimov, Rachel Carson, Charles Darwin, John Dewey, Albert Einstein, Jean Henri Fabre, Sigmund Freud, Stephen Jay Gould, Aldous Huxley, Julian Huxley, William James, Ernest Nagel, Bertrand Russell, Carl Sagan, Lewis Thomas, H.G. Wells and others.".
Originally published as: The sacred beetle and other great essays in science. 1984.
Science Books & Films (A.A.A.S.).
Young Adult.
Young Adult
Keywords: Science; Science